1996
DOI: 10.1152/jn.1996.76.2.698
|View full text |Cite
|
Sign up to set email alerts
|

Models of subthreshold membrane resonance in neocortical neurons

Abstract: 1. We obtained whole cell data from sensorimotor cortical neurons of in vitro slices (juvenile rats) and observed a low-frequency resonance (1-2 Hz) in their voltage responses. We constructed models of subthreshold membrane currents to determine whether a hyperpolarization-activated cation current (IH) is sufficient to account for this resonance. 2. Parameter values for a basic IH (BH) model were estimated from voltage-clamp experiments at room temperature. The BH model formed a component of a reduced membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
115
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(126 citation statements)
references
References 25 publications
10
115
0
1
Order By: Relevance
“…S1). This difference principally occurs, because Attwell and Laughlin (7) assumed R in,N and R in,A to be around 200 and 500 MΩ, respectively, based on in vitro recordings (30,31). However, our estimates of R in,N and R in,A values of 74 MΩ are in close agreement with in vivo measurements (13,14).…”
Section: Discussionsupporting
confidence: 54%
“…S1). This difference principally occurs, because Attwell and Laughlin (7) assumed R in,N and R in,A to be around 200 and 500 MΩ, respectively, based on in vitro recordings (30,31). However, our estimates of R in,N and R in,A values of 74 MΩ are in close agreement with in vivo measurements (13,14).…”
Section: Discussionsupporting
confidence: 54%
“…It has been observed that I NaP increases the impedance of neurons (Boehlen et al 2012;Curti et al 2008;Economo et al 2014;Gutfreund and Segev 1995;Hu et al 2002;Hutcheon et al 1996a;Hutcheon et al 1996b;Jacobson et al 2005;Klink and Alonso 1997;Manuel et al 2007;Pape and Driesang 1998;Saint Mleux and Moore 2000;Sun et al 2014;Wu et al 2001;Wu et al 2005;Yang et al 2009;Yaron-Jakoubovitch et al 2008). This increase in the membrane impedance is thus a function of membrane voltage, increasing as the neuron is depolarized towards the spike threshold.…”
mentioning
confidence: 99%
“…The latter, considered one of the most significant accomplishments in biophysics in the 20th century, provides a quantitative description of the electric potential across a cell membrane. The interaction between the real neuron and its artificial counterpart allows simulating artificial membrane or synaptic conductance (4,5), chemical or electronic inputs (6,7), and even connections with other neurons (8). Because the dynamic clamp falls midway between computational modeling and experimental electrophysiology, it affords the same degree of precision and freedom at the modeling level, while keeping the complexity of interaction with real neurons intact.…”
mentioning
confidence: 99%